2017
DOI: 10.1016/j.jana.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Among Women Living With HIV in Rural India

Abstract: A cross-sectional examination was conducted on Quality of Life (QOL) among Women Living with HIV (WLWH) in rural Andhra Pradesh, India. Baseline data were collected from 400 WLWH and their children. QOL was measured with 10 items from the Quality of Life Enjoyment and Satisfaction Questionnaire. Findings revealed low QOL scores; on a scale from 0 to 3, the mean QOL score was 0.38 (SD = 0.30). Depression symptoms were reported by 25.5%, internalized stigma was high, and most reported little to no social support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Based on our previous work (41), we also considered number of months since HIV diagnosis (natural-log transformed), number of side effects and number of Opportunistic Infections (linear and quadratic term) when VAS was the outcome. For the QOL outcome we considered as additional covariates social support and loneliness (dichotomized at <3 vs. ≥3 days in past week) (59). All potential covariates with unadjusted regression coefficients with a p-value ≤ 0.10 were included in multivariable regression analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous work (41), we also considered number of months since HIV diagnosis (natural-log transformed), number of side effects and number of Opportunistic Infections (linear and quadratic term) when VAS was the outcome. For the QOL outcome we considered as additional covariates social support and loneliness (dichotomized at <3 vs. ≥3 days in past week) (59). All potential covariates with unadjusted regression coefficients with a p-value ≤ 0.10 were included in multivariable regression analyses.…”
Section: Methodsmentioning
confidence: 99%
“…As far as we know, there has been no previous research among rural Indian women living with HIV that describes the association between the dimensions of stigma and health previously identified in our India-specific conceptual model (2, 27) Given the poor rates of adherence (41) and quality of life (41, 59) in this population, it is vitally important that we examine the role that stigma may play in these outcomes. The present paper aims to accomplish this, by examining the stigma fears, vicarious stigma, internalized stigma and the disclosure avoidant coping strategies reported by rural Indian women living with HIV as well as the association between these factors and the self-reported antiretroviral medication adherence and their perceived quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…According to the official report, the estimated number of people living with HIV (PLHIV) had exceeded 780,000 cases until 2014 and the numbers of AIDS-related deaths in 2014 were 21,000 cases in China (China Ministry of Health, 2016). At the advent of antiretroviral medication, HIV/ AIDS has been transformed from being considered a terminal illness to being a chronic and manageable condition (Oberjé et al, 2015). The availability of antiretroviral treatment (ART) coverage in China is approximately two-thirds, which makes overall mortality due to an AIDSrelated illness decrease significantly (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been theorized that internalized stigma can influence a HIV-infected person's mental health, social support, and HIV symptoms (Earnshaw and Chaudoir, 2009). A wealth of evidence has demonstrated that internalized stigma is negatively associated with divisive dimensions of health-related QOL, including perception of activity limitations, physical symptoms, and life satisfaction (Buseh et al, 2006(Buseh et al, , 2008Earnshaw et al, 2015;Fuster-Ruizdeapodaca et al, 2014;Nyamathi et al, 2017). In China, the majority of PLHIV have stigmatized feelings because HIV infection has been deemed as an immoral outcome, related to "losing face" in Chinese culture (Yang and Kleinman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Women may get stigmatized and isolated by their families and the society when they get severely sick, or may not be able to fulfill their traditional role of a caregiver, which may affect their own perceived HRQOL. More often, women who live in rural areas are often illiterate and lack employment, and report limited autonomy and less decision-making power, which can potentially affect their HRQOL, especially when dealing with a chronic illness (9).…”
mentioning
confidence: 99%